Review of the Newly Revised Marine Environmental Protection Law of the People's Republic of China - Zhenhua MIAO; Hongyan LIU (Haiyang Kaifa yu guanli, 2023)
In order to implement the construction of China's marine power and the reform of government institutions, while further improving the marine ecological environment, the newly revised Marine Environmental Protection Law of the People's Republic of China had made content adjustments to address the problems that had arisen in the implementation of previous laws. It had significantly reflected in clarifying the purpose and principles, improving governance systems, optimizing institutional mechanisms, strengthening supervision and management, and strictly assuming responsibilities. The paper comprehensively evaluated the newly revised Marine Environmental Protection Law of the People's Republic of China, aiming to provide specific suggestions for improving China's marine governance system and strive to propose effective improvement plans for the protection and management of China's marine ecological environment.